The Importance of The Spiritual Heritage of Uzbek Enlighteners in the Education of Youth - Sharipova Oqibat Aminjonovna (Research Parks Publishing LLC, 2021)
The article discusses the role of young people and their spirituality, the spiritual heritage of Uzbek enlighteners in the process of spiritual maturity. At the same time, the attitude of President Sh.M.Mirziyoev to the spiritual heritage of Uzbek enlighteners is given. Adaptation to water scarcity in Central Asia needs to be carried out jointly by all countries in the Central Asian region. According to the resolution, a number of measures have been developed to strengthen the protection of rivers, reservoirs, reservoirs and all sources of water supply from the harmful effects of industry, construction, transport, agriculture and other facilities.